Problems of modernization in Japan and intercultural interaction - L. B. Karelova (Vestnik MGIMO-Universiteta, 2012)
In the article, the author suggests an approach to the conceptualization of modernization problems that interprets them in the light of intercultural interaction. This approach helps particularly clear up the limits and framework of westernization specifying and making more precise the typology of modernization. In applying the approach to the analysis of Japanese modernization, the author brings about a hypothesis concerning mechanisms of cultural adaptation. These mechanisms contributed to reproduce some segments of Western pattern of modernization without destroying indigenous form of rationality and values. The author also makes an attempt to single out a set of basic ideas of such mechanisms in Japanese spiritual tradition.